2018
DOI: 10.32655/libres.2018.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Metadata model for organizing digital archives of tangible and intangible cultural heritage, and linking cultural heritage information in digital space

Abstract: Background. There are many digital archives in cultural domains, but there is no well-established metadata model which covers both tangible and intangible cultural heritage. Neither is there a well-established metadata model applicable to building digital archives by aggregating existing cultural heritage information. Objectives. The objective of this study is to develop a metadata model for digital archives of diverse cultural resources and dispersed communities, where metadata aggregation from different sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The so-called local elites are "insiders," while the relevant leaders and staff of the local government are "outsiders," and the local elites are from the public. The local elites give full play to the key link role, communicate with the local government by using their cultural discourse power, and then convey the government policies and guidance to the public (Wijesundara & Sugimoto, 2018).…”
Section: Andai Dance Heritage Protectionmentioning
confidence: 99%
“…The so-called local elites are "insiders," while the relevant leaders and staff of the local government are "outsiders," and the local elites are from the public. The local elites give full play to the key link role, communicate with the local government by using their cultural discourse power, and then convey the government policies and guidance to the public (Wijesundara & Sugimoto, 2018).…”
Section: Andai Dance Heritage Protectionmentioning
confidence: 99%
“…Determining the types of entities and processes related to intangible cultural heritage was needed to enable analysis and mapping according to conceptual models and data standards. The following working typology is based on several articles that researched data modelling of folklore and oral traditions (Nicolas 2005), archiving folk music and dance culture (Marolt et al 2009), organising digital archives of tangible and intangible cultural heritage (Wijesundara and Sugimoto 2018), modelling a representation protocol for traditional crafts (Zabulis et al 2022) and developing a web-based platform for traditional craft documentation (Partarakis et al 2022).…”
Section: Analysis Of Entities and Processes Related To Intangible Cul...mentioning
confidence: 99%
“…Several researchers have confirmed that an event-oriented approach is essential for modelling intangible cultural heritage, in contrast to the object-oriented or item-centric perspective that has been dominant thus far (Wijesundara and Sugimoto 2018). CIDOC-CRM E5 Event is a class comprising distinct, delimited, and coherent processes and interactions of a material nature in cultural, social, or physical systems.…”
Section: Processesmentioning
confidence: 99%
“…The Sampo model is a metadata model for creating cross-domain ontologies and linking data integration. On the empirical side, Wijesundara and Sugimoto (2018) discussed the metadata model for the representation of the relationships between tangible cultural heritage and intangible cultural heritage in the digital space and proposed a series of research studies based on the development and utilization of cultural resources problems and challenges. Qubumo et al (2013) took the life epics of ethnic minorities as the way of inheritance as the research object and formulated a metadata scheme to describe the sound records of traditional epics, including 19 parent elements and 104 child elements.…”
Section: Related Researchmentioning
confidence: 99%